Glioblastoma Molecular Mechanisms of Pathogenesis and Current Therapeutic Strategies - Ray, Swapan K.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Glioblastoma, the deadliest of all primary brain tumors, is heterogenic and has very complex pathology and multiple mechanisms of cell proliferation and growth. This book describes all the latest concepts about the molecular mechanisms of pathogenesis of glioblastoma and new therapeutic opportunities. The contributors to this book include basic scientists and clinicians, who are experts in the field, and dedicated investigators in finding novel strategies for treatment of glioblastoma. It is important for us to know the strategies we have accumulated so far for the management of this malignancy so that we can make further attempts to explore unknown avenues to combat it completely in the near future.
Overview of the Molecular Genetics and Molecular Chemotherapy of GBM -- Primary Brain Tumors: Characteristics, Practical Diagnostic and Treatment Approaches -- Pathology of Glioblastoma Multiforme -- Molecular Mechanisms of Pathogenesis in Glioblastoma and Current Therapeutic Strategies -- Aberrant Signalling Complexes in GBMs: Prognostic and Therapeutic Implications -- Role of Aberrant Cell Cycle in the Growth and Pathogenesis of Glioblastoma -- Adult Neural Stem Cells and Gliomagenesis -- Divide and Invade: The Dynamic Cytoskeleton of Glioblastoma Cells -- Aberrations of the Epigenome in Gliomas: Novel Targets for Therapy -- Chemotherapy for Glioblastoma: Past, Present, and Future -- Role of Angiogenesis in the Pathogenesis of Glioblastoma and Antiangiogenic Therapies for Controlling Glioblastoma -- Antiangiogenic Strategies for the Treatment of Gliomas -- Retinoids for the Treatment of Glioblastoma -- Molecular Mechanisms of Taxol for Induction of Cell Death in Glioblastomas -- Current Endeavors for Enhancing Efficacy of Paclitaxel for Treatment of Glioblastoma -- Dietary Polyphenols as Preventive and Therapeutic Agents in Glioblastoma -- Targeting Energy Metabolism in Brain Cancer with Restricted Diets -- Immunotherapy for Glioblastoma -- Potential of Nanobiotechnology in the Management of Glioblastoma Multiforme.
Keywords: Medicine; Oncology; Neurosciences; Biomedicine; Cancer Research; Oncology; Neurosciences